Interferon Receptor Trafficking and Signaling: Journey to the Cross Roads - Zanin, Natacha; Viaris de Lesegno, Christine; Lamaze, Christophe; Blouin, Cedric M. (Frontiers in Immunology, 2021)
Like most plasma membrane proteins, type I interferon (IFN) receptor (IFNAR) traffics from the outer surface to the inner compartments of the cell. Long considered as a passive means to simply control subunits availability at the plasma membrane, an array of new evidence establishes IFNAR endocytosis as an active contributor to the regulation of signal transduction triggered by IFN binding to IFNAR. During its complex journey initiated at the plasma membrane, the internalized IFNAR complex, i.e. IFNAR1 and IFNAR2 subunits, will experience post-translational modifications and recruit specific effectors. These finely tuned interactions will determine not only IFNAR subunits destiny (lysosomal degradation vs. plasma membrane recycling) but also the control of IFN-induced signal transduction. Finally, the IFNAR system perfectly illustrates the paradigm of the crosstalk between membrane trafficking and intracellular signaling. Investigating the complexity of IFN receptor intracellular routes is therefore necessary to reveal new insight into the role of IFNAR membrane dynamics in type I IFNs signaling selectivity and biological activity.